2019
DOI: 10.3390/su11092611
|View full text |Cite
|
Sign up to set email alerts
|

Visible Near Infrared Spectroscopy as a Green Technology: An Environmental Impact Comparative Study on Olive Oil Analyses

Abstract: The olive oil industry is a significant productive sector in the European Union and the related production process is characterised by practices and techniques associated with several adverse effects on the environment. In the literature, many works on the environmental impact assessment of the olive oil chain have been carried out but the effects of the analytical analyses procedures were considered to be negligible. Currently, the reduction of solvents and of energy consumption in the laboratory has become a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The authentication of EVOO requires the application of fast, reliable, and cost-effective analytical procedures with no or little sample manipulation, such as NIR spectroscopy. Besides, NIR spectroscopy can be considered a green technology because it involves a low environmental impact . The assignment of bands in the NIR spectrum is straightforward, but the application of chemometrics is required to extract the maximum relevant information from the spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The authentication of EVOO requires the application of fast, reliable, and cost-effective analytical procedures with no or little sample manipulation, such as NIR spectroscopy. Besides, NIR spectroscopy can be considered a green technology because it involves a low environmental impact . The assignment of bands in the NIR spectrum is straightforward, but the application of chemometrics is required to extract the maximum relevant information from the spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…From that condition it is shown that a compound with lower percentage concentration will need a more complicated data pretreatment [8]. Moreover, result showed that NIR spectroscopy could be used as a green technology [11][12] that is needed nowadays to reduce the usage of chemicals. As shown in [11], comparing the environmental impact contribution between the usage of chemical and NIR analysis, it was found that an average value of 36 NIR analysis is equal to one chemical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The economic significance of olive industries to the European Union is unquestionable. Europe contributed almost 70% of the world olive oil production in the 2018–2019 harvest year campaign and the resultant revenue was to the tune of five billion euro [ 1 ]. This large and continuously expanding industry is also associated with many negative environmental problems stemmed from waste production and inappropriate disposal, soil depletion, and atmospheric emissions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%